Burden of Motor Neuron Diseases in a Tertiary Care Center of Eastern Nepal: A Case Series with Literature Review - Rauniyar, Vivek K.; Khan, Sajjad Ahmed; Gautam, Sakshyam; Devkota, Diskhya; Parajuli, Surya Bahadur (Journal of BP Koirala Institute of Health Sciences, 2024)
A Motor Neuron Disease (MND) is a collective term for progressive neurological disorders that affect primary motor neurons. The primary aim of our study was to explore the spectrum of MNDs, their sex distribution, the prevalence of different subtypes, diagnostic modalities, and interventional strategies to alter the natural course of the disease. This study was conducted from May 2020 to July 2023, over a period of three years, at our tertiary care center. During this time, we identified a total of five cases of Amyotrophic Lateral Sclerosis (ALS), four cases of Progressive Bulbar Palsy (PBP), and one case of Progressive Muscular Atrophy (PMA). The typical age of presentation was over 40 years, with one exception being an 18 years old male. There was a slight female predominance in terms of sex distribution. Regarding treatment, Riluzole remained the mainstay, though the treatment outcomes were not particularly favorable.